Association between folate intake and risk of head and neck squamous cell carcinoma: An overall and dose–response PRISMA meta-analysis. Issue 42 (October 2017) - Fan, Chengchao; Yu, Siwei; Zhang, Si; Ding, Xiaojun; Su, Jian; Cheng, Zhigang
Abstract : Abstract: The results of published studies about the relationships between folate intake and risk of head and neck squamous cell carcinoma (HNSCC) remained inconsistent. Hence, a comprehensive and dose–response meta-analysis was performed to clarify the association between folate intake and HNSCC risk. The electric searches of Pubmed, Medline, and EMBASE databases were performed to identify the studies examining the relationship between folate intake and HNSCC risk on April 5, 2017. According to the inclusion criteria, finally 9 studies were included in this meta-analysis. The pooled odds ratios (ORs) with 95% confidence intervals (CIs) were used to evaluate the strength of associations. Dose–response analysis was conducted to quantitate the relationship between dietary folate intake and HNSCC risk. The pooled OR for assessing the risk of HNSCC and folate intake in the highest level versus lowest level was 0.505 (95% CI 0.387–0.623). The linearity model of dose–response analysis indicated that with increased 100 μg/d folate intake, the risk of HNSCC decreased 4.3% degree (OR 0.957, 95% CI 0.935–0.980). These results indicate that folate is a protective nutrient against HNSCC carcinogenesis.